2020
DOI: 10.1002/cncy.22242
|View full text |Cite
|
Sign up to set email alerts
|

Insulinoma‐associated protein 1 (INSM1) is a robust marker for identifying and grading pancreatic neuroendocrine tumors

Abstract: BACKGROUND: Pancreatic neuroendocrine tumor (PNET) is a diagnostic challenge with limited samples in not only identification but grading. Prior studies have shown insulinoma-associated protein 1 (INSM1) to be a robust marker in identifying PNETs from other solid pancreatic tumors on resection specimens. In this study, we investigated the utility of INSM1 not only for identifying PNETs but also for grading in cell blocks (CBs) and surgical resections (SRs). METHODS: A search for PNET cases between 2000 and 2019… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 19 publications
2
16
0
Order By: Relevance
“…The other conventional NE biomarkers are not as sensitive for the pure NET, and CGA failed to stain NET component of a MiNEN NET sample, suggesting that INSM1 could be a more sensitive biomarker for diagnosing pure NETs or identifying NET components in mixed cases [ 54 ]. In fact, in an analysis of cell block samples, INSM1 displayed 100% sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) for differentiating NET from non-NET pancreatic tumors, as SPN (solid pseudopapillary neoplasm), ACC (acinar cell carcinoma), and PDAC (pancreatic ductal adenocarcinoma) samples were always INSM1 negative (unlike SYP which was positive for SPN), making it a useful marker for excluding possible non-NET diagnoses [ 54 , 55 ]. Since it has a high NPV for PDAC, it can be useful for excluding exocrine pancreatic tumors in a differential diagnosis.…”
Section: Insm1 Expression In Pancreatic Netsmentioning
confidence: 99%
See 1 more Smart Citation
“…The other conventional NE biomarkers are not as sensitive for the pure NET, and CGA failed to stain NET component of a MiNEN NET sample, suggesting that INSM1 could be a more sensitive biomarker for diagnosing pure NETs or identifying NET components in mixed cases [ 54 ]. In fact, in an analysis of cell block samples, INSM1 displayed 100% sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) for differentiating NET from non-NET pancreatic tumors, as SPN (solid pseudopapillary neoplasm), ACC (acinar cell carcinoma), and PDAC (pancreatic ductal adenocarcinoma) samples were always INSM1 negative (unlike SYP which was positive for SPN), making it a useful marker for excluding possible non-NET diagnoses [ 54 , 55 ]. Since it has a high NPV for PDAC, it can be useful for excluding exocrine pancreatic tumors in a differential diagnosis.…”
Section: Insm1 Expression In Pancreatic Netsmentioning
confidence: 99%
“…In a study, INSM1 expression was given an H-score (H score considered the level of expression (0-3) and the percentage of cells stained and then weighed for a score between 0 and 300) in 55 pancreatic NETs with variable tumor gradings. The H-score was approximately 30 for G3 pancreatic NETs, 229 for G1 and 266 for G2 tumors [ 55 ]. The results for INSM1 expression was identical for both pancreatic NETs on cell block and surgical resection.…”
Section: Insm1 Expression In Pancreatic Netsmentioning
confidence: 99%
“…38 Recent studies demonstrated the diagnostic utility of INSM1 in other organs when the obtained tissue was scant in either a small biopsy or a cell block of cytology specimens as an alternative or effective stand-alone neuroendocrine marker. 13,15,33,39-43 Taken together, INSM1, especially when combined with either CT or mCEA, may potentially replace a panel of the traditional MTC markers or be the first line of choice among the MTC immunohistochemical markers when the obtained lesional tissue is quantitatively limited.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the diagnostic utility of INSM1 as a neuroendocrine marker was demonstrated in pulmonary neuroendocrine tumors, 11,12 pancreatic neuroendocrine tumors, 13,14 gastrointestinal tract tumors, 15 peripheral neuroblastic tumors, 16 laryngeal neuroendocrine carcinoma, 17 head and neck tumors, 18 Merkel cell carcinoma of the skin, 19 gynecologic tumors, mammary carcinoma, and prostate adenocarcinoma with neuroendocrine differentiation. 20 Studies have demonstrated that INSM1 is a highly specific marker for neuroendocrine tumors, and it is suggested that INSM1 may serve as a novel therapeutic target.…”
Section: Introductionmentioning
confidence: 99%
“…The calculation for the H score is as follows: 1× (% 1+ tumor cells) + 2× (% 2+ tumor cells) + 3 × (% 3+ tumor cells) as previously described in pancreatic neuroendocrine tumors. 11 Average H scores were calculated in each laryngeal NEC and for the different grades.…”
Section: Interpretation Of Immunohistochemical Findingsmentioning
confidence: 99%